Perception of Public Islam on Performance and Providing Public Services in Padangsidempuan City - Feriza Yetti Siregar (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2020)
Public service is a matter that is closely associated with bureaucracy. Five factors are related to mission, accountability, consequences, power, and culture. Mission will determine the public services system competence in responding to dynamics that occur in the community accurately and efficiently. Method in this research was qualitative method, which was designed with descriptive research and phenomenology approaches through interviews and observations. Based on the research, the results showas follow: First, the perception of Islamic society in Padangsidimpuan on performance of Dinas Kependudukan dan Pencatatan Sipil (DKPS) in providing public services in 2014 was still far from their hope, and it hasn’t met in their satisfaction category especially Islamic society. Second, factors that influence the achievement of DKPS Padang Sidimpuan in providing public services in 2014 are human resources and financial factors. Besides, there are some supporting factors: leadership, resources, culture ministry, institutional, and related regulation. Third, factor that hold up the performance of DKPS Padangsidimpuan in providing public services in 2014 is organization structure. The other factors are such as the lack of officers responding to society who need the information and the lack of officers’ hospitality when they communicate to public. Fourth, the solution is given from Islamic society to improve public services at DKPS Padangsidimpuan for the next year: education, experiences, training, motivation to the staff and officer at DKPS Padangsidimpuan.